(3GdGSgGe GdfSHj degGQGJ EOGQI GdPGJ hJfXje GdGfaYGdGJ aj GdJfHD HGdJecjf GdfaSj ddJdGejP Phj UYhHGJ GdJYde HGdeQMdI GdGYOGOjI (B/s - (3gOjQ GdbWH YjSi eMeO Ndjd,s; (3YeQh QeVGf YWGjGs; (3ESQGA NGdO eMeOs (2024)
(3gOaJ GdOQGSI Edi GdJYQa Ydi GdYdGbI Hjf egGQGJ EOGQI GdPGJ hGdJecjf GdfaSj hGdYdGbI Hjf JfXje GdGfaYGdGJ hGdJecjf GdfaSj, heOj ESgGe cdkG ef egGQGJ EOGQI GdPGJ hJfXje GdGfaYGdGJ aj GdJfHD HGdJecjf GdfaSj ddJdGejP Phj UYhHGJ GdJYde HGdeQMdI GdEYOGOjI , hJchfJ YjfI GdOQGSI ef (B(320) (3JdejkPG hJdejPI ef JdGejP GdeQMdI GdEYOGOjI , hGSJNOeJ GdOQGSI ebjGS egGQGJ EOGQI GdPGJ hebjGS JfXje GdGfaYGdGJ hebjGS GdJecjf GdfaSj, hJhUdJ fJGFL GdOQGSI Edi hLhO YdGbI ehLHI Hjf GdOQLI GdcdjI degGQGJ EOGQI GdPGJ hGdOQLI GdcdjI ddJecjf GdfaSj hcPdc Hjf GHYGO cdG ef egGQGJ EOGQI GdPGJ h`CHYGO GdJecjf GdfaSj hhLhO YdGbI WQOjI ehLHI Hjf JfXje GdGfaYGdGJ hCHYGOg eY GdJecjf GdfaSj hCHYGOg dOi GdJdGej``P Phj UYhHGJ GdJYde HGdeQMdI GdEYOGOjI, ajeG YOG HYO EYGOI GdJbjje GdeYQaj ddGfaYGdGJ eY CHYGO GdJecjf GdfaSj ZjQ OGd GMUGFjG, hcPdc jecf GdJfHD ef egGQGJ EOGQI GdPGJ hCHYGO JfXje GdGfaYGdGJ HGdJecjf GdfaSj ddJdGejP Phj UYhHGJ GdJYde HGdeQMdI GdEYOGOjI(B. s
The study aims to identify the relationship between self-management skills and psychological empowerment, the relationship between emotion regulation and psychological empowerment, and the extent to which both self-management skills and emotion regulation contribute to predicting the psychological empowerment of students with learning disabilities in the preparatory stage. The study sample consisted of (320) male and female students from the preparatory stage. Preparatory school. The study used the self-management skills scale, the emotion regulation scale, and the psychological empowerment scale prepared by the researcher. The results of the study found that there is a positive relationship between the total score of self-management skills and the total score of psychological empowerment, as well as between the dimensions of both self-management skills and the dimensions of psychological empowerment, and the existence of a positive direct relationship between emotion regulation and its dimensions with psychological empowerment and its dimensions among students with learning disabilities in the preparatory stage, with the exception of After the cognitive reappraisal of emotions with the dimensions of psychological empowerment,. Likewise, it is possible to predict from the self-management skills and the dimensions of emotion regulation the psychological empowerment of students with Learning disabilities in middle school.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
. (3HHdjhLQGajG(B: (3UaMGJ (B134-147.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGdEfLdjRjI(B.s
Keywords: (3GdGWaGd HWjFh GdJYde s; (3GdGWaGd GdThGPs; (3egGQGJ EOGQI GdPGJ s -- (3JfXje GdGfaYGdGJ s -- (3GdJecjf GdfaSjs